A miRNA Signature in Human Cord Blood Stem and Progenitor Cells as Potential Biomarker of Specific Acute Myeloid Leukemia Subtypes. Issue 8 (August 2015) - Cattaneo, M.; Pelosi, E.; Castelli, G.; Cerio, A.M.; D′angiò, A.; Porretti, L.; Rebulla, P.; Pavesi, L.; Russo, G.; Giordano, A.; Turri, J.; Cicconi, L.; et al.
<x xml:space="preserve">Abstract</x> MicroRNAs (miRNAs) are important regulators of several cellular processes. During hematopoiesis, specific expression signatures have been reported in different blood cell lineages and stages of hematopoietic stem cell (HSC) differentiation. Here we explored the expression of miRNAs in umbilical cord blood stem (HSC) and progenitor cells (HPC) and compared it to unilineage granulocyte and granulo‐monocyte differentiation as well as to primary blasts from patients with acute myeloid leukemia (AML). CD34 + CD38‐ ad CD34 + CD38 + cells were profiled using a global array consisting of about 2000 miRNAs. An approach combining bioinformatic prediction of miRNA targets with mRNA expression profiling was used to search for putative biologically enriched functions and networks. At least 15 miRNAs to be differentially expressed between HSC and HPC cell population, a cluster of 7 miRNAs are located in the q32 region of human chromosome 14 (miR‐377–3p, ‐136–5p, 376a–3p, 495–3p, 654–3p, 376c–3p and 381–3p) whose expression decreased during the early stages of normal myelopoiesis but were markedly increased in a small set of AML. Interestingly, miR‐4739 and ‐4516, two novel microRNA whose function and targets are presently unknown, showed specific and peculiar expression profile during the hematopoietic stem cells differentiation into unilineages and resulted strongly upregulated in almost all AML subsets. miR‐181, ‐126–5p, ‐29b–3p and ‐22–3p resulted dis‐regulated in specific leukemias phenotypes. This study provides the first evidence of a miRNA signature in human cord blood stem and progenitor cells with a potential role in hematopoietic stemness properties and possibly in leukemogenesis of specific AML subtypes. J. Cell. Physiol. 230: 1770–1780, 2015. © 2014 Wiley Periodicals, Inc.